2013
DOI: 10.1007/s10856-013-5001-7
|View full text |Cite
|
Sign up to set email alerts
|

In vitro study of dual drug-eluting stents with locally focused sirolimus and atorvastatin release

Abstract: Within the context of novel stent designs we developed a dual drug-eluting stent (DDES) with an abluminally focussed release of the potent anti-proliferative drug sirolimus and a luminally focussed release of atorvastatin with stabilizing effect on atherosclerotic deposits and stimulating impact on endothelial function, both from biodegradable poly(L-lactide)-based stent coatings. With this concept we aim at simultaneous inhibition of in-stent restenosis as a result of disproportionally increased smooth muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 33 publications
2
23
0
Order By: Relevance
“…This is in part based on the localization of target and non-target cells in immediate vicinity of the drug delivery device and the use of compounds with high passive permeability. One of the approaches to enhance cell targeting may be the restricted loading on the drug delivery device, as previously reported, showing dual loading of stents with atorvastatin on the luminal side and sirolimus on the abluminal side [27]. In addition, derivatives of the lead compound sirolimus and their influence on smooth muscle cell proliferation and viability have been tested, showing a pronounced impact on proliferation without affecting cell viability compared to cells treated with paclitaxel, a compound demonstrating high cytotoxic effects [28,29].…”
Section: Discussionmentioning
confidence: 84%
“…This is in part based on the localization of target and non-target cells in immediate vicinity of the drug delivery device and the use of compounds with high passive permeability. One of the approaches to enhance cell targeting may be the restricted loading on the drug delivery device, as previously reported, showing dual loading of stents with atorvastatin on the luminal side and sirolimus on the abluminal side [27]. In addition, derivatives of the lead compound sirolimus and their influence on smooth muscle cell proliferation and viability have been tested, showing a pronounced impact on proliferation without affecting cell viability compared to cells treated with paclitaxel, a compound demonstrating high cytotoxic effects [28,29].…”
Section: Discussionmentioning
confidence: 84%
“…The CHOICE trial might shed some light on this question [49]. Possibly, biocompatible, polymer-based abluminal or dual, and side-selective coatings as well as other innovative, polymer-free drug reservoirs might be applicable [14,50,51]. Common DES are summarized in Table 1.…”
Section: Polymers For Cardiovascular Stents: Bioderived and Resorbablementioning
confidence: 99%
“…In our own published studies, absorbable polymer stent coatings based on PLLA were developed. This research focused on the one hand on physicochemical characterization of the obtained coating with regard to morphology and the impact of processing parameters on polymer degradation [132] and on the other hand on the establishment of novel dual drug-eluting stents (DDES) with an abluminally focussed release of the potent anti-proliferative drug sirolimus and a luminally focussed release of atorvastatin with stabilizing effect on atherosclerotic deposits and stimulating impact on endothelial function [252]. During physicochemical characterization of established PLLA coatings, we observed that achieved structural integrity via a spray-coating process was maintained after crimping and full expansion of stent prototypes.…”
Section: Des Equipped With Biodegradable Polymeric Coatingsmentioning
confidence: 99%